The impact of digitalization on the green development of the marine economy: evidence from China’s coastal regions - Jin, Xin; Li, Mengxue; Lei, Xue (Frontiers in Marine Science, 2024)
Under the impetus of the new generation of technological revolution, digitalization offers new opportunities for the green development of the marine economy. Utilizing data from 11 coastal Chinese provinces and cities between 2011 and 2020, this paper constructs a comprehensive index system for the green development of the marine economy. Based on this, a fixed effects model is used to explore the impact of digitalization on the green development of the marine economy and its underlying mechanisms. The findings indicate that digitalization effectively promotes the green development of the marine economy, with this effect being more pronounced in regions bordering “the Belt and Road” initiative. Mechanism tests indicate that digitalization promotes the green development of the marine economy by raising the comprehensive development level of ports. When breaking down the components of port development, it is found that improving the port location quotient plays a more crucial role than port radiation intensity in how digitalization promotes the green development of the marine economy. Additionally, environmental regulation exerts a U-shaped moderating effect on the relationship between digitalization and the green development of the marine economy. Based on these findings, it is recommended to use digital technologies and data, expedite the development of marine big data platforms, integrate port resources, optimize port operations, and apply environmental regulation policies judiciously to promote efficient marine resource management and sustainable marine economic development.